The Relationship of Psychosocial Factors on Amphetamine Substance Addiction in Rehabilitation Medan Plus, Indonesia - Yusuf Wibisono; Elmeida Effendy; Vita Camellia (Budapest International Research and Critics University, 2022)
Amphetamines and other amphetamine-like substances are known to interfere with other mental and physical conditions, such as impaired social functioning. The relationship between substance-related disorders and social factors, socioeconomic factors play an important role in the prognosis of patients with substance-related disorders. In fact, amphetamine use has been found to be associated with several markers of social adjustment disability such as crime, other substance use, unemployment, suicide and homicide. This study aims to determine the relationship between psychosocial factors and amphetamine dependence in Medan Plus rehabilitation. This research is a one-time unpaired observational analytic study with a cross sectional approach. The research sample was obtained by means of non-probability sampling consecutive sampling type by recruiting 76 subjects based on age, gender, education level and occupation as risk factors for amphetamine dependence, which were patients with amphetamine dependence who were treated at the Medan Plus Rehabilitation for more than 1 year. In identifying the period of use and substance use, an ASSIST (Assement Smoking and Substance Involvement Screening Test) assessment was carried out, it was called amphetamine independent, the value was ASSIST 0-26, and the amphetamine dependence was ASSIST 27. There was a significant relationship between age (p=0.017), gender (p=0.001) and amphetamine dependence. There was no significant relationship between education (p=0.505), occupation (p=0.220) and amphetamine dependence. Factors influencing amphetamine dependence were gender (OR= 15.93), occupation (OR= 0.556), and age (OR= 0.106).